Effects of Hyperoxia on Mitochondrial Homeostasis: Are Mitochondria the Hub for Bronchopulmonary Dysplasia? - Xuefei, Yu; Xinyi, Zhao; Qing, Cai; Dan, Zhang; Ziyun, Liu; Hejuan, Zheng; Xindong, Xue; Jianhua, Fu (Frontiers in Cell and Developmental Biology, 2021)
Mitochondria are involved in energy metabolism and redox reactions in the cell. Emerging data indicate that mitochondria play an essential role in physiological and pathological processes of neonatal lung development. Mitochondrial damage due to exposure to high concentrations of oxygen is an indeed important factor for simplification of lung structure and development of bronchopulmonary dysplasia (BPD), as reported in humans and rodent models. Here, we comprehensively review research that have determined the effects of oxygen environment on alveolar development and morphology, summarize changes in mitochondria under high oxygen concentrations, and discuss several mitochondrial mechanisms that may affect cell plasticity and their effects on BPD. Thus, the pathophysiological effects of mitochondria may provide insights into targeted mitochondrial and BPD therapy.